PENGGUNAAN GAYA BAHASA REFETISI DALAM SURAH AL-JIN (SEBUAH TINJAUAN STILISTIKA): THE USE OF REFETITIONAL LANGUAGE STYLE IN SURAH AL-JIN (A STILISTIC REVIEW) - Hasibuan, Sammad (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2022)
Abstract: This study aims to describe the types of repetition language styles contained in Surah Al-Jin, verse 1 to verse 28. The method used in this research is descriptive-qualitative method. Because the expected results are not in the form of numbers, but in the form of a descriptive presentation. The approach used is a stylistic approach, especially the style of repetition or repetition of Gorys Keraf's perspective. The results showed that there are five types of repetition language styles contained in Surah Al-Jin, namely anaphora, epistropha, mesodiplosis, epizeuksis and tautotes. Among the five types, the most widely used are anaphora, epistropha and tautotes repetition types. For the use of the type of mesodiplosis, only found a few times. This study is expected to be able to add to the treasures of stylistic scholarship, especially examining the suras in the Qur'an from the aspect of using the style of repetition or tikrr from the perspective of Gorys Keraf.